Utilizing low-frequency ultrasound as a countermeasure to asphalt-resin-paraffin deposition in oil pipelines - Nazarenko, Ivan; Nesterenko, Tetiana; Nesterenko, Mykola; Bernyk, Iryna (Academic journal Industrial Machine Building Civil Engineering, 2022)
The experimental data on the low-frequency ultrasound effect on asphalt-resin-paraffin deposits (ARPD) occurring in oil transportation through pipelines are presented. As a result of the empirical data statistical processing, a correlation was obtained, which enables the prediction of the ultrasonic exposure time required to remove ARPD from the surface of the pipes. The temperature regime changed from the time of ARPD formations exposure to the ultrasonic influence was analyzed. The proposed algorithm for finding the ultrasonic treatment optimal operational parameters can be used not only in the selection of ultrasonic equipment parameters, which control ARPD in pipelines but also in the run-in hole ultrasonic equipment’s operating parameters selection in certain fields conditions